Bolus feeding has no effect on cerebral hemodynamics, irrespective of gestational age. - Bembich, Stefano; Cont, Gabriele; Bua, Jenny; Orlando, Chiara; Di Benedetto, Donatella; Demarini, Sergio (J Matern Fetal Neonatal Med, 2017)
OBJECTIVE: By multichannel near-infrared spectroscopy, we studied if gestational age has any influence on preterm cerebral hemodynamics, during bolus feeding. METHODS: Oxy-haemoglobin (HbO), as cerebral blood flow estimate, and the ratio between HbO and total haemoglobin (HbO/HbTot), as cerebral oxygenation estimate, were assessed in 40 stable premature infants, during a 10 min bolus feeding. RESULTS: We found no effect of any of the gestational ages studied (25-34 weeks) either on cerebral blood flow or on oxygenation, during a bolus feeding procedure. CONCLUSIONS: Bolus feeding appears not to affect cerebral hemodynamics of uncritically preterm infants, irrespective of gestational age.
Keywords: Cerebrovascular Circulation; Enteral Nutrition; Female; Gestational Age; Heart Rate; Humans; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Male; Oxygen; Oxyhemoglobins; Spectroscopy, Near-Infrared